Income inequality and trust in national governments in Central, Eastern and Southeastern Europe - Christian Alexander Belabed; Mariya Hake (Oesterreichische Nationalbank (OeNB), 2018)
Using unique evidence from the OeNB Euro Survey, this paper sheds light on the correlation between the distribution of income and trust in national governments in ten Central, Eastern and Southeastern European (CESEE) countries between 2009 and 2015. By applying multilevel modeling to account for the hierarchical structure of the data, our main findings indicate that trust in national institutions increases with the individual's position in the regional income distribution but it overall declines with the increase of regional and country income inequality. This result is valid across different measures of income inequality and despite the slight decrease of income inequality over the period. Our analysis shows that perceived high corruption and weak rule of law are key determinants of distrust in national governments, while the negative link between income inequality and trust in national governments is more pronounced in the non-EU countries in our sample.
Keywords: D1; D63; E24; H21; P23; 330; Income inequality; Institutional trust; Multilevel models